(untitled) (Revista Contexto & Educação, 2021)
Between the 1970s and the 1990s, a project to train untitled teachers called Logos II was developed in some regions of Brazil. The program adopted the educational technology of distance learning via modular. The curriculum of Logos II contained 28 subjects, divided into two categories (General and Special) which, after completing their studies, enabled the teacher-student to qualify as a high school teacher. Thus, the article on screen aims to elaborate a history of the curriculum in the 1970s based on the analysis of the curriculum of the Logos II project. In addition, we will highlight the concepts of technical education that structured the Brazilian curriculum, and consequently the curriculum structure of the Logos II Project. The documents related to the Logos II project were used as sources, as well as the laws and other documents related to the theme. As a theoretical-methodological framework, we used the concept of curriculum by Goodson (2012) and the understanding of historical source analysis by Ginzburg (1989; 2008) and Pesavento (2008). The results indicate that at the time of the project’s implementation, the Brazilian curriculum received major international influences, due to the bilateral agreements that marked the construction of the Logos II curriculum.